(untitled) (Bangladesh Journal of Botany, 2011)
Two mungbean (Vigna radiata (L.) Wilczek) genotypes (GK48 - flood tolerant and BARImug5- flood susceptible) were flooded at vegetative and flowering stages for 5 and 10 days, respectively. Flooding damaged the lateral roots of GK48 wholly, but it recovered quickly by forming numerous adventitious roots. Flooding significantly reduced photosynthetic rate (Pn) and leaf water potential (Ψ1) in both the genotypes but GK48 tended to regain Pn and Ψ1 during postflooding phase. It appeared that GK48 withstands flooding to a great extent. Key words: Water potential; Mungbean; Root growth; Photosynthesis DOI: 10.3329/bjb.v39i2.7487 Bangladesh J. Bot. 39(2): 241-243, 2010 (December)